Laparoscopic treatment of biliary hepatic cysts: short- and medium-term results - Neri, Vincenzo (2006)
Background. The aim of this study was to evaluate the postoperative morbidity and, in the medium-term results, the incidence of relapses in the laparoscopic treatment of non-parasitic hepatic cysts (NPHC) and polycystic liver disease (PCLD). Patients and methods. From 1999 to 2003, 12 patients with NPHC and 3 patients with PCLD with few large cysts in the anterior hepatic segments underwent laparoscopic fenestration and deroofing. Results. There were no conversions and no mortality; the mean operative time was 55 min for NPHC and 120 min for PCLD. Postoperative morbidity comprised two patients with bronchopneumonic infiltrations and in one patient with PCLD ascites resolved spontaneously. All the patients experienced resolution of the symptomatology. Follow-up was carried out from 3 to 38 months (mean 18 months). There was no relapse of the disease. Discussion. The preoperative selection of patients is fundamental to program the surgical treatment. Laparoscopy can be considered a safe and efficacious treatment for NPHC and PCLD.